Pemanfaatan Teknologi Pemasaran Digital dan Manajemen Keuangan di Desa Maron Kabupaten Kediri: Utilization of Digital Marketing Technology and Financial Management in Maron Village Kediri District (Jurnal Pengabdian Perikanan dan Kelautan: Piskarias Ministerium, 2023)
Penelitian ini bertujuan untuk meningkatkan pengetahuan dan keterampilan wirausaha dalam pemasaran digital serta transisi ke pembukuan digital di Desa Maron, Kecamatan Banyakan Kabupaten Kediri. Program pelatihan ini melibatkan 18 peserta dari kelompok ibu PKK Desa Maron Kecamatan Banyakan Kabupaten Kediri. Pelatihan mencakup pemberian materi tentang pemasaran digital melalui platform Shopee dan TikTok, serta pengenalan aplikasi "Money Manager" untuk pembukuan digital. Hasil evaluasi menunjukkan bahwa program pelatihan ini berhasil meningkatkan pemahaman peserta tentang pemasaran digital, penggunaan platform online, dan manfaat pembukuan digital. Para peserta juga mampu mengaplikasikan pengetahuan yang mereka peroleh dalam usaha mereka, menghasilkan peningkatan penjualan, mutu produk, dan efisiensi operasional. Mayoritas peserta berhasil melakukan transisi dari pembukuan manual ke pembukuan digital dengan aplikasi "Money Manager", yang membantu mereka dalam mengelola keuangan usaha secara lebih efisien. Hasil program pelatihan ini memiliki dampak positif dan berkelanjutan dalam pengembangan bisnis para peserta. Mereka kini memiliki pengetahuan dan keterampilan untuk memanfaatkan teknologi digital dalam pemasaran produk mereka. Program ini juga memberikan inspirasi bagi usaha mikro kecil dan menengah di Desa Maron Kecamatan Banyakan Kabupaten Kediri untuk melakukan inovasi dan pertumbuhan ekonomi lokal dan peningkatan kualitas hidup masyarakat.   This research aims to enhance the knowledge and entrepreneurial skills in digital marketing and the transition to digital bookkeeping in Maron Village, Kediri Regency. The training program involved 18 participants from the PKK (Family Welfare Empowerment) group, selected through a rigorous selection process. The training included providing materials on digital marketing through platforms like Shopee and TikTok, as well as introducing the "Money Manager" application for digital bookkeeping. Evaluation results indicated that the training program successfully improved participants' understanding of digital marketing, the use of online platforms, and the benefits of digital bookkeeping. Participants were also able to apply the knowledge they gained to their businesses, resulting in increased sales, product quality, and operational efficiency. The majority of participants successfully transitioned from manual bookkeeping to digital bookkeeping using the "Money Manager" application, which helped them manage their business finances more efficiently. The outcomes of this training program had a positive and sustainable impact on the development of participants' businesses. They now possess the knowledge and skills to leverage digital technology in marketing their products. The program also served as an inspiration for micro and small businesses in Maron Village and its surrounding areas to innovate and grow. This research provides a positive contribution to supporting local economic growth and improving the quality of life for the community in Maron Village. It is hoped that similar programs can be implemented and expanded in the future to create an even greater impact.